User-Centered Development of an Online Platform for Drug Dosing Recommendations in Pediatrics - Rödle, Wolfgang; Wimmer, Stefan; Zahn, Julia; Prokosch, Hans-Ulrich; Hinkes, Bernward; Neubert, Antje; Rascher, Wolfgang; Kraus, Stefan; Toddenroth, Dennis; Sedlmayr, Brita (Applied Clinical Informatics, 2019)
Background Drug therapy in pediatric patients is a complex process. Children are subject to continuous growth and variation in drug-metabolizing enzyme activity, requiring continuous adaption of dosages. In Germany, currently no publicly available database exists that provides evidence-based information on drug dosages in pediatrics. For local drug dosing support, a prototype database has been developed within the Children's Hospital, Erlangen. A user-centered development process was initiated to establish an online platform for evidence-based dosing recommendations, as well as pharmacological and pharmaceutical drug information in pediatrics.Objectives The objectives of the study were to survey the demand for such a platform and to assess the usability of the different versions of the developed system.Methods The developed prototype was evaluated in a pluralistic walkthrough with prospective end users. After a redesign, the second prototype of the online platform underwent an online usability testing based on a tailored questionnaire and the System Usability Scale (SUS) (n = 12).Results Eleven of 12 participants expressed a demand for an online platform for pediatric dosing recommendations. The majority of the participants requested the integration of extended features, such as drug–drug interaction alerts, or information on adverse effects, pharmacokinetics, and pharmacodynamics. Particularly noteworthy is the demand for an online calculator; 5 of a total of 15 participants explicitly requested a calculator for dosages (based on age, weight, body surface) and glomerular filtration rate. The usability of the second prototype was rated “good to excellent” with a median SUS of 81.25.Conclusion Local domain experts demand an online platform for pediatric dosing recommendations. The application of the user-centered design approach enabled the development of a prototype suitable for practical use. Multiple additional required functionalities have been identified, whereby the importance of an online calculator for patient–individual dosing recommendations was particularly emphasized.
Keywords: decision support techniques; drug therapy; computer-assisted; online systems; knowledge bases; pediatric dosages